Profitability Determinants in Rural Banks: The Moderating Role of Ownership - Nyimas Nunin Anisah Baidury; Anggraeni Anggraeni (Transpublika Publisher, 2025)
The profitability of BPRs still faces serious challenges due to relatively low and fluctuating ROA performance compared to other banks. This raises the need to re-examine the financial factors and ownership structure that could potentially affect the performance of BPRs. This study investigates the factors affecting the profitability of rural banks (BPR) in Malang Raya and Pasuruan, Indonesia, with a focus on operational efficiency, credit risk, liquidity, bank size, and ownership structure. Using panel data from the Financial Services Authority (OJK), the study applies multiple linear regression to analyze 168 valid observations after data cleaning. The results reveal that operational efficiency (OER) and credit risk (NPL) negatively affect ROA, while larger bank size also reduces profitability. Liquidity, measured by Loan to Deposit Ratio (LDR) and Loan to Asset Ratio (LAR), does not significantly impact ROA. Furthermore, private ownership amplifies the negative effect of credit risk on profitability. These findings suggest that rural banks should focus on improving operational efficiency, managing credit risk more effectively, and addressing management inefficiencies, particularly in larger institutions. The study also highlights the importance of balancing profit maximization with robust risk management in privately owned banks. The implications of this research are valuable for policymakers and bank managers aiming to enhance financial performance and sustainability in the rural banking sector.